Absolute Allergy and Immunology Board Review - Mahmoudi, Massoud; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a comprehensive review of allergy and immunology, specifically dedicated as a board review preparation. The book is a collective effort and participation of over 90 well known allergists, immunologists, and rheumatologist who are academician and or practitioners. Chapters are presented in a " Case-Based" format. Each chapter presents 2 cases; each case is followed by multiple choice questions/ answers and discussions. Each chapter also offers a list of specific references used in the text, that will enhance the readers' portfolio of resources. Allergy and Immunology Board Review is a must-have resource for allergy & immunology fellows-in-training and all allergy practitioners as well as any medical provider including residents, medical students and allied health who rotate in allergy divisions. .
Chapter 1. Innate and Adaptive Immunity -- Chapter 2. Immune cells and Functions -- Chapter 3. Allergic Eye Disease -- Chapter 4. Rhinitis -- Chapter 5. Otitis -- Chapter 6. Asthma -- Chapter 7. Occupational Asthma -- Chapter 8. Exercise-induced Asthma -- Chapter 9. Cough and Allergic Diseases -- Chapter 10. Cystic Fibrosis -- Chapter 11. Hypersensitivity Pneumonitis -- Chapter 12. Allergic Bronchopulmonary Aspergillosis -- Chapter 13. Food Allergy -- Chapter 14. Eosinphilic Esophagitis -- Chapter 15. Urticaria & Angioedema -- Chapter 16. Atopic Dermatitis -- Chapter 17. Mastocytosis -- Chapter 18. Insect Allergy -- Chapter 19. Latex Allergy -- Chapter 20. Facial Mask Allergy -- Chapter 21. Drug Allergy -- Chapter 22. Rheumatoid Arthritis -- Chapter 23. Reiter Syndrome and Reactive Arthritis -- Chapter 24. Lyme Disease -- Chapter 25. Vasculitis -- Chapter 26. B-cell Deficiency -- Chapter 27. T-cell Deficiency -- Chapter 28. Combined Immunodeficiency Disease -- Chapter 29. HIV Infection -- Chapter 30. Anaphylaxis -- Chapter 31. Antihistmines and corticosteroids -- Chapter 32. Bronchodialators -- Chapter 33. New asthma therapeutics -- Chapter 34. Subcutaneous Immunotherapy -- Chapter 35. Sublingual Immunotherapy. .
Keywords: Allergy; Immunology; Allergology; Immunology